Discovering computers 2006 a gateway to information : web enhanced : complete - Shelly, Gary B.; Cashman, Thomas J.; Vermaat, Misty (Shelly Cashman series, 2005)
Provides current and thorough introduction to computers by integrating usage of the World Wide Web with the printed text. This text offers a complete solution to successfully teach students basic computer concepts with new exercises, case studies, and online tools on the Companion Web site. For the past three decades, the Shelly Cashman Series? has effectively introduced computers to millions of students-consistently providing the highest quality, most up-to-date, and innovative materials in computer education.